PENGARUH SUBSTITUSI LIMBAH CAIR INDUSTRI TAHU PADA MEDIA TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI JAMUR TIRAM PUTIH (Pleurotus ostreatus) SEBAGAI SUMBER BELAJAR BIOLOGI - Alfisyah, Yuni Ida; Susanto, Agus (Bioedukasi Jurnal Pendidikan Biologi, 2014)
This study aims to get a dose of the best concentrations of liquid waste in order to produce rapid mycelial growth and production of white oyster mushrooms with optimal fresh weight. In this study using Analysis of Variance (ANOVA) One Direction with four treatments, each treatment be repeated six times. The treatments tested were (A) the concentration of liquid waste 25%/L water/ treatment, (B) the concentration of liquid waste 30%/L water/treatment (C) concentration of liquid waste 35%/L water/treatment and (D) control. The results showed that the concentration of industrial wastewater know 25%/L water/highest treatment effect on the growth and production of white oyster mushroom (Pleurotus ostreatus) with a mean weight of 129.33 gr fresh row A; B 105.5 gr; C 76.17 gr; and D 90.83 gr. The results could be used as a source of learning biology at the high school level with the subject matter of the class X Waste and Recycling Waste. In addition, this study also can be a reference for researchers and the general public.Â Kata Kunci: limbah cair, jamur, produksi, biologi.